Academic Procrastination Behavior on Language Students in English Education Study Program of IAIM Sinjai - Kareba, Andi Muammar; Harmilawati; Aminah, Sitti (Universitas Islam Ahmad Dahlan (UIAD), 2022)
This research aims to discover the causes of the language learners of English Education study program in Islamic Institute of Muhammadiyah Sinjai procrastination behaviour. This research is categorized as a phenomenological research by using qualitative approach. The subject of this research is the students of English Education Study Program of IAI Muhammadiyah Sinjai. The techniques of data collection used are observation, interview, and documentation and the technique of data analysis is using Miles and Huberman theory. The result shows that the students are intended to do the academic procrastination behaviour which caused by: (1) delay in starting and completing task at hand, (2) delay in doing assignments, (3) time gap between planned and actual performance, and (4) doing other activities that are more fun than doing the task that must be done. Keywords: academic procrastination, language student, procrastination behaviour